Assistance for Fruit Traders in Frozen Fruit Technology: Solutions to Overcome Product Damage and Increase Revenue - Kartika Sari Lubis (RESPINARIA : Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, contributing around 60% to the national Gross Domestic Product (GDP) and absorbing more than 97% of the workforce in the formal sector. In this context, fruit traders as part of MSMEs play a vital role in the food supply chain, connecting producers with end consumers and ensuring products remain fresh and of good quality. However, fruit traders face various challenges, such as product damage due to limited storage technology, price fluctuations, and limited adoption of digital technology. To overcome these issues, processing fruit into frozen products is suggested as an effective solution. Nearly rotten fruits can be processed into frozen products, which have a longer shelf life and can be marketed more widely. This transformation not only helps traders avoid losses but also opens up new business opportunities, especially in the culinary sector. Post COVID-19 pandemic, MSMEs in Indonesia have also shown significant adaptation through digitalization, with 62% of MSMEs having utilized digital technology by 2022. This confirms the importance of digitalization in improving the competitiveness of MSMEs in the modern era.